Medicine Inventory Information System and Indicator - Mohamad Tagor, Shahzarul Fikri; MUHD YUNUS, MOHD AMIN (Applied Information Technology And Computer Science, 2022)
The advances in medicine and pharmaceuticals are various types of drugs or medicines that sometimes have similar functions. Because different doctors may use different drugs for the same function for treatment, many more clinics use one type of drug that works to treat a particular disease. Therefore, the search tool used is very important to choose the error in giving the medicine to the patient. Searching for medications on the medication shelf is also time consuming for medications that need to be given to patients are correct. Then a Drug Inventory and Indicator Information System was developed using a structured user based on the 'Internet of things' (IoT) for drug search activities for users who misused drugs for patients and more orderly calculation of drug stocks on drug shelves. The Waterfall model used as the system development methodology includes five phases related to the analysis phase, design phase, implementation phase, testing phase, and maintenance phase. The software used in the development of this system is Microsoft Visual Studio and Microsoft Access as the Database data system. The system is also developed using an LED indicator search system, each Arduino for the process of finding the exact location of medicines before going through the system, then on the shelves of medicines. With the existence of this system, it can increase the efficiency in finding drugs accurately among other types of drugs in a shorter time and in turn can help pharmacy workers at the Paya Besar Clinic.